Rodents and humans are able to detect the odour of L-Lactate. - Valentina Mosienko; Andy J Chang; Natalia Alenina; Anja G Teschemacher; Sergey Kasparov (PLoS ONE)
L-Lactate (LL) is an essential cellular metabolite which can be used to generate energy. In addition, accumulating evidence suggests that LL is used for inter-cellular signalling. Some LL-sensitive receptors have been identified but we recently proposed that there may be yet another unknown G-protein coupled receptor (GPCR) sensitive to LL in the brain. Olfactory receptors (ORs) represent the largest family of GPCRs and some of them are expressed outside the olfactory system, including brain, making them interesting candidates for non-olfactory LL signalling. One of the "ectopically" expressed ORs, Olfr78 in mice (Olr59 in rats and OR51E2 in humans), reportedly can be activated by LL. This implies that both rodents and humans should be able to detect the LL odour. Surprisingly, this has never been demonstrated. Here we show that mice can detect the odour of LL in odour detection and habituation-dishabituation tasks, and discriminate it from peppermint and vanilla odours. Behaviour of the Olfr78 null mice and wildtype mice in odour detection task was not different, indicating that rodents are equipped with more than one LL-sensitive OR. Rats were also able to use the smell of LL as a cue in an odour-reward associative learning task. When presented to humans, more than 90% of participants detected a smell of LL in solution. Interestingly, LL was perceived differently than acetate or propionate-LL was preferentially reported as a pleasant sweet scent while acetate and propionate were perceived as repulsive sour/acid smells. Subjective perception of LL smell was different in men and women. Taken together, our data demonstrate that both rodents and humans are able to detect the odour of LL. Moreover, in mice, LL perception is not purely mediated by Olfr78. Discovery of further LL-sensitive OR might shed the light on their contribution to LL signalling in the body.